Perancangan Buku Panduan Sebagai Sarana Informasi Warisan Budaya Kuliner di Pasar Lama Tangerang untuk Kalangan Remaja Dewasa 17-25 Tahun - Friska Bella Ananda; Hendi Thamrin (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This guidebook is designed to introduce the culinary delights of Pasar Lama Tangerang to young adults aged 17-25 who may have a limited appreciation for culinary heritage due to a lack of informative media about Pasar Lama Tangerang's cuisine. The author has crafted the guidebook to be unique and engaging, providing various types of information. Additionally, the book offers an interactive element for readers, who can participate in a contest scheduled at specific times by placing stickers in the book once they have tried 50 different foods listed. The research methodology employs a qualitative approach, aiming to describe and obtain detailed data from field results, yielding in-depth and contextual insights. This research utilizes data collection methods such as interviews, questionnaires, direct observations of the research site, and literature searches for relevant journals and articles. The design methodology adopts the design thinking approach to find solutions through creative thinking, with iterative processes to address failures and create innovative work. The visual concept of the guidebook features a simple yet modern and cool design, supported by semi-realistic illustrations to enhance its appeal. The guidebook is expected to effectively convey information and broaden readers' knowledge about the culinary offerings of Pasar Lama Tangerang.